2009
DOI: 10.1016/j.bbrc.2009.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic stretch induces cyclooxygenase-2 gene expression in vascular endothelial cells via activation of nuclear factor kappa-β

Abstract: Vascular endothelial cells respond to biomechanical forces, such as cyclic stretch and shear stress, by altering gene expression. Since endothelial-derived prostanoids, such as prostacyclin and thromboxane A 2 , are key mediators of endothelial function, we investigated the effects of cyclic stretch on the expression of genes in human umbilical vein endothelial cells controlling prostanoid synthesis: cyclooxygenase-1 (COX-1), cyclooxygenase-2 (COX-2), prostacyclin synthase (PGIS) and thromboxane A 2 synthase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…Another NFAT5 target that was identified by our initial microarray approach and confirmed by following expression analyses of hypertension-exposed arteries appears to be Ptgs2 (Cox2). Originally described to be transcriptionally regulated by NFAT5 in renal epithelial cells upon hypertonic stimulation (22), COX2 expression in mechanoactivated cells is thought to be controlled by the transcription factor NF-kB (54). Interestingly, recent reports suggest that NFAT5 is capable of forming an enhanceosome with NF-kB, which is required to recruit p300 (55).…”
Section: Discussionmentioning
confidence: 99%
“…Another NFAT5 target that was identified by our initial microarray approach and confirmed by following expression analyses of hypertension-exposed arteries appears to be Ptgs2 (Cox2). Originally described to be transcriptionally regulated by NFAT5 in renal epithelial cells upon hypertonic stimulation (22), COX2 expression in mechanoactivated cells is thought to be controlled by the transcription factor NF-kB (54). Interestingly, recent reports suggest that NFAT5 is capable of forming an enhanceosome with NF-kB, which is required to recruit p300 (55).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is also upregulated in mouse artery VSMCs exposed to cyclical stretch for 2 h [76]. NFĸB also plays a role in COX-2 transcription in HUVECs exposed to cyclical stretch [77]. COX-2 and thromboxane synthase enzymes are involved in the stepwise breakdown of arachidonic acid into prostacyclin and thromboxane-A2.…”
Section: Stretch-regulated Genes Affecting the Inflammatory Response mentioning
confidence: 99%
“…2.5-fold in endothelial cells. 72 Prior studies have also shown that TGF beta-1 (2 ng/mL) can promote COX-2 protein expression in benign kerationocytes. 73 BMP-2 (100 ng/mL) increased expression of COX-2 mRNA in primary osteoblasts rapidly within several hours, and the induction of PGE 2 was 45% higher in the wild type compared with COX-2 knockout cells.…”
mentioning
confidence: 99%